2018
DOI: 10.1080/09638288.2018.1483434
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of participating in a client-centred ADL intervention after stroke

Abstract: The intervention contributed to transparency, which appeared to enable and support the client's sense of ownership of daily activities and rehabilitation after stroke. Implications for rehabiliation A client-centred activities of daily living intervention seems to contribute to transparency, where persons with stroke can discover and understand their new ability and situation after stroke. A client-centred rehabilitation situation seems to enable clients to actively engage in their own rehabilitation process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…In order to further deepen the conceptualization and describe the relationship between the categories, a theoretical coding was used [26]. The results from previous studies that describe the importance of sharing and transparency in a client-centred intervention for rehabilitation after stroke [21,22] were used to create the four categories presented in the results. The coding frame is presented in Supplementary Appendix 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to further deepen the conceptualization and describe the relationship between the categories, a theoretical coding was used [26]. The results from previous studies that describe the importance of sharing and transparency in a client-centred intervention for rehabilitation after stroke [21,22] were used to create the four categories presented in the results. The coding frame is presented in Supplementary Appendix 2.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the development of theory, a previous study was performed which showed that people 6-12 months after a stroke had the drive and need to use ICT in their everyday lives, despite having physical and cognitive impairments resulting from the stroke [20]. Another previous study within the research group showed that occupational therapists and people after a stroke emphasized the importance of "sharing and transparency" during the rehabilitation process in order to facilitate a person-centred approach [21,22]. The concept of "sharing" included building a therapeutic relationship, sharing professional knowledge and sharing an understanding of the patients' experiences, activities and goals [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCSCI developed to be the CADL intervention comprised in turn different steps and strategies in which the OT's role initially was to create a relationship with the client to jointly work out how the training would be designed in the activities that were important for the client to perform. Using that problem-solving strategy, the clients had the opportunity in collaboration with an OT to designing goals, plan training, evaluating, and formulating new goals (65,66). The group who received the CADL intervention was compared with people who received the UADL.…”
Section: Client-centered Adl-interventionmentioning
confidence: 99%
“… 19 Moreover, they experienced that the intervention enabled them to feel as owners of their own rehabilitation process. 32 33 This suggests that the effect of the CADL intervention on healthcare usage might be related to a changed healthcare-seeking behaviour of an activated patient. Similar results have also been found in other settings, showing an inverse association between patient activation (knowledge, skills and confidence) and healthcare usage, that is, patients with higher levels of activation had lower healthcare usage.…”
Section: Discussionmentioning
confidence: 99%